Effects of Experimental Sleep Restriction on Energy Intake, Energy Expenditure, and Visceral Obesity - Covassin, Naima; Singh, Prachi; McCrady-Spitzer, Shelly K; St Louis, Erik K; Calvin, Andrew D; Levine, James A; Somers, Virend K (Journal of the American College of Cardiology, 2022)
Although the consequences of sleep deficiency for obesity risk are increasingly apparent, experimental evidence is limited and there are no studies on body fat distribution. The purpose of this study was to investigate the effects of experimentally-induced sleep curtailment in the setting of free access to food on energy intake, energy expenditure, and regional body composition. Twelve healthy, nonobese individuals (9 males, age range 19 to 39 years) completed a randomized, controlled, crossover, 21-day inpatient study comprising 4 days of acclimation, 14 days of experimental sleep restriction (4 hour sleep opportunity) or control sleep (9 hour sleep opportunity), and a 3-day recovery segment. Repeated measures of energy intake, energy expenditure, body weight, body composition, fat distribution and circulating biomarkers were acquired. With sleep restriction vs control, participants consumed more calories (P = 0.015), increasing protein (P = 0.050) and fat intake (P = 0.046). Energy expenditure was unchanged (all P > 0.16). Participants gained significantly more weight when exposed to experimental sleep restriction than during control sleep (P = 0.008). While changes in total body fat did not differ between conditions (P = 0.710), total abdominal fat increased only during sleep restriction (P = 0.011), with significant increases evident in both subcutaneous and visceral abdominal fat depots (P = 0.047 and P = 0.042, respectively). Sleep restriction combined with ad libitum food promotes excess energy intake without varying energy expenditure. Weight gain and particularly central accumulation of fat indicate that sleep loss predisposes to abdominal visceral obesity. (Sleep Restriction and Obesity; NCT01580761).